De Novo discovery of nonstandard macrocyclic peptides as noncompetitive inhibitors of the Zika Virus NS2B-NS3 protease - Nitsche, Christoph; Leuthold, Mila; Klein, Christian D. (ACS medicinal chemistry letters, 2019)
The Zika virus presents a major public health concern due to severe fetal neurological disorders associated with infections in pregnant women. In addition to vaccine development, the discovery of selective antiviral drugs is essential to combat future epidemic Zika virus outbreaks. The Zika virus NS2B-NS3 protease, which performs replication-critical cleavages of the viral polyprotein, is a promising drug target. We report the first macrocyclic peptide-based inhibitors of the NS2B-NS3 protease, discovered de novo through in vitro display screening of a genetically reprogrammed library including noncanonical residues. Six compounds were selected, resynthesized, and isolated, all of which displayed affinities in the low nanomolar concentration range. Five compounds showed significant protease inhibition. Two of these were validated as hits with submicromolar inhibition constants and selectivity toward Zika over the related proteases from dengue and West Nile viruses. The compounds were characterized as noncompetitive inhibitors, suggesting allosteric inhibition.
Gesehen am 17.09.2019